1 - Producing Anthropological Knowledge in and of Southern Africa: A Case Study of the Anthropology Southern Africa Journal - Morreira, Shannon (Journal of Higher Education in Africa, 2022)
This article conducts an archival examination of the Anthropology Southern Africa journal (formerly the South African Journal of Ethnology/Suid- Afrikaanse Tydskrif vir Etnologie), in keeping with Allen and Jobson’s (2016) call for anthropology to examine its own archives, as spaces of knowledge production which act as indexes of power. The article moves through three eras of the journal, between 1978 and 2020, showing how it evolved from being the home of volkekunde anthropology under apartheid, to a space for the production of anthropological knowledge by both established and nascent voices from the global South. Turning attention to the demographic minutiae of praxis within journals enables the start of a conversation about who was making anthropological know edge at different moments in history, and what sort of knowledge was made.